The role of Apigenin in testicular damage in experimental ischemia-reperfusion injury in rats - Skondras, I (Hippokratia, 2015)
BACKGROUND: Testicular torsion is an acute urologic emergency occurring in male newborns, children or adolescents. Prolonged ischemia for more than six hours can lead to irreversible testicular damage. Surgical detorsion allows reperfusion and is the only treatment currently available. The aim of this study was to evaluate the antioxidant effect of apigenin (APG) on the testicular ischemia-reperfusion (I/R) injury. METHODS: Forty-two Wistar rats were randomly divided into five groups. Sham group underwent operation of the left testis. In the torsion-detorsion groups C(15) and C(120), the left testis was rotated 1080(o) for three hours. The treatment groups Ap(15) and Ap(120) received the same surgical procedure as groups C(15) and C(120), but APG was administered intravenously at the same time of detorsion via the right femoral vein. Left orchiectomy was performed 15 min after detorsion at groups C(15) and Ap(15), and at 120 min at groups C(120) and Ap(120) for histopathologic and immunohistochemical evaluation. RESULTS: In I/R-untreated groups C(15) and C(120), there was a moderate to severe distortion of the tubules with lesions that varied between grades III and IV according to histopathological finding. In APG-treated groups Ap(15) and Ap(120), most of the lesions showed injuries of grades II and III with mild and moderate histopathological features. In Terminal deoxynucleotide transferase dUTP Nick End Labeling (Tunel) assay, APG-treated animals showed a statistically significantly decreased number of apoptotic cells compared to groups C(15) and C(120). CONCLUSION: Intravenous administration of APG seems to have a protective effect on testicular ischemia-reperfusion injury after testicular torsion and detorsion. Hippokratia 2015; 19 (3): 225-230.